Synthesis and Characterization of 2,3,4-Trihydroxy-5-methyl Xanthone as Antimalarial Compound - Dhina Fitriastuti; Jumina Jumina; Priatmoko Priatmoko (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Synthesis of xanthone derivatives had been conducted to obtain new antimalaria active compounds. The characterization of the synthesized xanthones was also conducted. Synthesis of xanthone was conducted from the raw material of hydroxybenzoic acid and phenol derivatives using Eaton's reagent via acylation-dehydration reaction by modified Grover, Shah and Shah (GSS) method. The synthesis of 2,3,4-trihydroxy-5-methyl xanthone was carried out using gallic acid, o-cresol and Eaton's reagent.The mixture was heated for 3 h at 80 °C to yield 2,3,4-trihydroxy-5-methyl xanthone in 43% yield as dark red viscous liquid. The results of IR, 1H-NMR and 13C-NMR analysis of sampleshowed that the compound2,3,4-trihydroxy-5-methyl xanthonehas successfully synthesized.